DESCRIPTIVE ANALYSIS OF THE AFFECTIVE-RELATIONAL SECTOR AND THE PSYCHIC DYNAMICS IN POSTPARTUM WOMEN (PRÁXIS EM SAÚDE, 2025)
Women are in constant psychic development, and there are always possibilities for modifications, restructurings, and reintegrations of their personality. In this sense, the present work provides an understanding of women in their life cycle, considering that there are three critical periods of transition that represent stages of personality development: adolescence, pregnancy, and climacteric. These periods are characterized by complex biological and metabolic transformations, which may generate imbalances resulting from changes in social roles, readaptations, interpersonal and intrapsychic adjustments, and identity changes. During pregnancy, women undergo an important moment of restructuring in their lives and in the roles they perform. For this study, the descriptive method with a qualitative approach will be used. The qualitative study consists of a descriptive and interpretative perspective of the contents presented by the participants, seeking to attribute meaning to these phenomena. The objective of this work was to describe the aspects of the Affective-Relational (A-R) sector and the psychic dynamics of women in the postpartum period, and to achieve this objective, three women in the postpartum period were analyzed.
Keywords: Affective-relational; Postpartum; Women; Psychic dynamics